PERANAN INSTRUMEN EKONOMI DALAM MENGURANGI EMISI GAS CO2 Ã¢â‚¬Å“SUATU PERSPEKTIF UNTUK INDONESIAÃ¢â‚¬Â - Fachruddin, Kemas (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Indonesia still using common and control (CAC) instruments in controllingenvironmental problems. Law No 23 year 1997 and decree of the ministerand others regulations related to the law were established based ontop-down policy approach. Environmental problems in most cases areeffective to be controlled using common and control policy, however inissues of pollution or emission control, economic instrument or marketbased instrument is effective compare to the CAC. Another reason isflexibility of the instrument. This empirical study is intended to analyzehow an instrument economy is useful in controlling CO2 emission. DICEmodel (Dynamic Integrated and Climate Change Economic ) or sometimecalled Three–Box model system is one of economic models which isused for controlling CO2 emission in response to potential threat ofglobal warming. Emission of CO2 from fossil fuel is taxed throughoptimation of the model. Emission control rate is policy variable. Modelsystem equations are solved using General Algebraic Modeling System(GAMS). Optimum scenario is occurred where value of rate of socialpreference 5%. Model outcome suggest that abatement cost havingrange between 0.1-6.7% of GDP and reduction of emission in range of20 - 80% of current emission rate for the period of 1990-2019. In optimalcondition, model suggest that appropriate emission tax for fossil fuelhaving range of 0.002 – 0.024 USD per liter or equivalent to 3.90-40.35USD carbon tax per ton of fossil fuel coal having range 1,95 -20,25USD per ton CO2.